2018
DOI: 10.22159/ijap.2018.v10s1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanocurcumin on Cisplatin-Induced Acute Kidney Injury: A Focus on Nrf2 and Keap1

Abstract: Objective: This study aimed to investigate the effect of nanocurcumin (NC) against cisplatin-induced acute kidney injury, focusing on Nrf2 and Keap1.Methods: Male Sprague-Dawley rats (n=23) were divided into five groups (Control, CP, CP+Cur, CP+50 NC, and CP+100 NC) and sacrificed 7 days aftertreatment. Whole kidneys were collected for reverse transcription polymerase chain reaction (RT-PCR) analysis of Nrf2 and Keap1.Results: There were no statistically significant differences in the RT-PCR results among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The same study also showed increased levels o and glutathione due to nanoformulation treatment. Pandhita et al [60] reported a…”
Section: Organic Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study also showed increased levels o and glutathione due to nanoformulation treatment. Pandhita et al [60] reported a…”
Section: Organic Nanostructuresmentioning
confidence: 99%
“…The same study also showed increased levels of Nrf2 and glutathione due to nanoformulation treatment. Pandhita et al [60] reported a nano-based formulation of curcumin against cisplatin-induced renal injury. They observed upregulation of Keap1 and Nrf2 activation due to nanoformulation treatment.…”
Section: Organic Nanostructuresmentioning
confidence: 99%